Household indebtedness: How global and domestic macro-economic factors influence credit card debt default in Malaysia - Theong, May Jin; Osman, Ahmad Farid; Yap, Su Fei (Faculty of Economics and Administration, University of Malaya, 2018)
Malaysia has one of the highest household debts relative to gross domestic product in the Asia region. High indebted households have negative net worth and prone to default even during mild shocks. In most economies including Malaysia, household loan default is dominated by mortgages. In Malaysia, however, credit card debt default rate has been growing faster than mortgage default rate. Thus, this paper analyses how combined global and domestic macroeconomic factors impact on credit card nonperforming loan (NPLs) in Malaysia. Estimates from the Autoregressive Distributed Lags (ARDL) model highlights that in the long run, credit card NPLs are procyclical as strong domestic real output reduces credit card default. The study shows positive global crude oil price shocks reduces the credit card NPLs while a stressed global financial market condition has a reverse effect on credit card NPLs. Further, consumer price index negatively relates to credit card NPLs while monetary policy affects NPLs whereby a cut back of the overnight policy rate reduces credit card debt default.